Correlates of Delayed Initial Contact to Emergency Services among Patients with Suspected ST-Elevation Myocardial Infarction - Osayi Lawani; Nicholas Gorman; Fiona Gorman; Jiries Ganim; Stefano Sdringola-Maranga (Cardiology Research and Practice)
Background. Early diagnosis and treatment of a patient displaying symptoms of myocardial ischemia is paramount in preventing detrimental tissue damage, arrhythmias, and death. Patient-related hospital delay is the greatest considerable cause of total delay in treatment for acute myocardial infarction. Objective. To identify patient characteristics contributing to prehospital delay and ultimately developing health interventions to prevent future delay and improve health outcomes. Methods. A retrospective chart review of 287 patients diagnosed with ST-elevation myocardial infarction (STEMI) was evaluated to examine correlates of patient-related delays to care. Results. Stepwise logistic regression modeling with forward selection (likelihood ratio) was performed to identify predictors of first medical contact (FMC) within 120 minutes of symptom onset and door-to-balloon (DTB) time within 90 minutes. Distance from the hospital, being unmarried, self-medicating, disability, and hemodynamic stability emerged as variables that were found to be predictive of FMC within the first 120 minutes after symptom onset. Similarly, patient characteristics of gender and disability and having an initial nondiagnostic electrocardiogram emerged as significant predictors of DTB within 90 minutes. Conclusions. Individual attention to high-risk patients and public education campaigns using printed materials, public lectures, and entertainment mediums are likely needed to disseminate information to improve prevention strategies. Future research should focus on identifying the strengths of prehospital predictors and finding other variables that can be established as forecasters of delay. Interventions to enhance survival in acute STEMI should continue as to provide substantial advances in overall health outcomes.